Typification of two aquatic plant names described by Linnaeus from highly heterogeneous original elements: Sagittaria sagittifolia (Alismataceae) and Sparganium erectum (Typhaceae). Issue 2 (13th December 2022) - Ferrer‐Gallego, P. Pablo; Grebenjuk, Alexey V.; Iamonico, Duilio; Iberite, Mauro; Talavera, Salvador
Abstract: The original material of the Linnaean names Sagittaria sagittifolia and Sparganium erectum both represent more than one taxon. This had previously led to a reluctance to resolve the nomenclature of these two species, led some to consider the application of the names doubtful, and even led some to propose that Sp. erectum should be treated as a nomen ambiguum. Incorporating study of the Linnaean correspondence and several unpublished manuscripts, we discuss these names and typify them here. Sagittaria sagittifolia is lectotypified with a specimen from LINN. Sparganium erectum is lectotypified with an illustration of "Platanaria sive Butomon" published by Dodoëns in 1616. An epitype is also designated for Sp. erectum because the lectotype is demonstrably ambiguous and the name cannot be applied to a currently recognized taxon with certainty. The previously designated lectotype of Sp. natans is also discussed, as is the importance of previously unrecognized original material in the Johann Georg Gmelin Herbarium at LE.